2022
DOI: 10.1021/acssensors.2c01824
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Urinalysis with One Drop of Sample Using an Aggregation-Induced Emission Luminogen under the Coffee-Ring Effect

Abstract: Development of a practical point-of-care test for urinalysis is crucial for early diagnosis and treatment of chronic kidney disease (CKD). However, the classical gold standard detection method depends on sophisticated instruments and complicated procedures, impeding them from being utilized in resource-limited settings and daily screening. Herein, we report a rapid point-of-care device for the simultaneous quantification of microalbuminuria and leukocyte using one drop of urine. A luminogen (TTVP) with an aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…In Figure F, the general method is not sensitive enough to the target concentration. As shown in Table S3, we compared recent reported work on visual fluorescent sensing based on the coffee-ring effect. The results showed that the proposed strategy was more recognizable in visualization. Figure S6 demonstrates the good reproducibility of our method.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure F, the general method is not sensitive enough to the target concentration. As shown in Table S3, we compared recent reported work on visual fluorescent sensing based on the coffee-ring effect. The results showed that the proposed strategy was more recognizable in visualization. Figure S6 demonstrates the good reproducibility of our method.…”
Section: Resultsmentioning
confidence: 99%
“…Leukocytes in urine can reflect the occurrence of a body infection or inflammation. Situ, Zheng, and co-workers reported an AIE-based POCT method for rapidly detecting and quantifying microalbuminuria and leukocytes using one drop of urine . The AIE probe TTVP activated its NIR fluorescence in the presence of albumin and leukocyte via hydrophobic or electrostatic interactions.…”
Section: Follow the Breadcrumbs: Detection And Monitoringmentioning
confidence: 99%
“…Situ, Zheng, and co-workers reported an AIE-based POCT method for rapidly detecting and quantifying microalbuminuria and leukocytes using one drop of urine. 565 The AIE probe TTVP activated its NIR fluorescence in the presence of albumin and leukocyte via hydrophobic or electrostatic interactions. In combination with a smartphonebased detection device, the fluorescence signals were wellseparated.…”
Section: Virus Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This advective flow is caused by the liquid from the interior of the drop rushing toward the TPCL, with the TPCL remaining pinned, to replenish the liquid that is lost from the TPCL due to evaporation. The ubiquitousness of the coffee ring formation has meant that the presence of such ring-like deposits at the TPCL, occurring during the evaporation of drop containing any type of particle, is generically denoted as the “coffee ring”. The inherent self-assembly process associated with the coffee ring formation has been extensively utilized to self-assemble different types of micro/nanoparticles and chemical species for applications, such as pre-concentrating chemical samples before their analyses, , sensitive detection of organic and biomolecules and their properties, triggering size-dependent particle separation, and fabricating a variety of materials/structures/functional devices, such as immunoassays, photonic and plasmonic crystals, conducting wires, porous films, and scaffolds of different materials, and microcantilevers . At the same time, the “coffee ring” formation has also several disadvantages, such as the formation of nonuniform coating/patterning, formation of trench-like and raised ridge structures during three-dimensional (3D) printing with metal nanoparticle ink, , etc.…”
Section: Introductionmentioning
confidence: 99%